Discussion on São Paulo Mobility Plans - Maes, Fernanda Lucia; Oliveira Mesquita, Amanda; Batista de Morais, Mariana (International Journal of Engineering and Management Sciences, 2021)
Since urbanization rising and urban demographic increase, urban transportation has been an important life quality aspect and a strategic decision for cities. Mobility seems to follow citizens’ behavior and be influenced by urban cultural changes at the same pace it influences back the city routine and resident’s conduct. The discussion around the future of mobility gained new magnitude nowadays since some sort of vehicles have proved themselves as the cause of significant environmental impact, while others showed themselves as alternatives of low impact for different reasons – from quality public transportation to individual transport with minimized emissions. The city of São Paulo in Brazil published its Master Plan in 2014 and its Mobility Plan in 2015, analyzing the current situation and proposing a future for the city’s transportation system. This paper intends to analyze both plans, construe the popular participation in their formulation and application, discuss how data and strategy were presented and whether they are aligned with other countries’ thinking on the subject. As a city of over 10 million inhabitants, in a Metropolitan Region of 39 cities with over 20 million inhabitants, the transportation system of São Paulo is not an easy or single-solution issue. It is known the need for a combination of different transportation modes, requiring likewise new visions for all methods. Owing to the fact that modes complete each other and, in that manner, may reach a wider range of options for the population to plan daily life, then a system with a great variety of modes ensures the best functioning of them all. This paper focuses on an outsider view that searches for answers and solutions on the São Paulo transportation system, having as a base what is considered outstanding in the world for this issue.